Facile, Stereocontrolled Synthetic Route towards Bis-functionalised Pyrrolizidines - Lindner, Marcin; Krasiński, Antoni; Jurczak, Janusz (Synthesis, 2018)
A simple and convenient method for the synthesis of bis-functionalised pyrrolizidines starting from readily available N-Cbz-l-prolinal is described. This aldehyde was converted within two concise steps to the corresponding aminoepoxides, which were separately subjected to regioselective cyclisation induced by a reductive cleavage of the Cbz protecting group. The versatile and concise strategy holds great potential for practical application in the straightforward preparation of pyrrolizidine-based drugs and natural products.
Keywords: alkaloids; heterocycles; diastereoselective synthesis; asymmetric epoxidation; cyclisation; tandem reaction